Examination of Textiles with Mathematical and Physical Methods - Ehrmann, Andrea; Blachowicz, Tomasz (Springer International Publishing : Imprint: Springer, 2017)
This book presents basic knowledge on the examination of textile materials, from fibers to yarns and knitted or woven fabrics, using mathematical and physical methods. Besides typical textile test procedures, defined by well-known standards, the book aims at showing new ways to examine textile materials and giving an overview of the possibilities as well as problems occurring when methods from other areas are transferred into the examination of textiles. The contents range from apparently simple measurements, such as resistance of conductive coatings on woven fabrics, to diffraction measurements on woven fabrics, to optical examination of knitted fabrics by mathematical approaches to study yarn hairiness and cover factor.